GRAMMATICAL COHESION CONJUNCTION OF 99 CAHAYA DI LANGIT EROPA NOVEL BY HANUM SALSABIELA RAIS AND RANGGA ALMAHENDRA - Eko Yulianto (Universitas Indraprasta PGRI, 2020)
Abstract: This article contains the results of research on discourse analysis of 99 Cahaya di Langit Eropa which is one of the best-selling novel in Indonesia. In addition to positioning the novel as a literary work, also need to analyze the novel in terms of linguistics. The purpose of this study was to determine the grammatical cohesion contained in the novel, specifically the conjuncture grammatical cohesion.This study uses qualitative content analysis techniques, sampling by way of reduction of the content of the novel. This research analyzes the use of grammatical conjunctions cohesion on the novel, which consists of grammatical cohesion adversative conjunctions, temporal, causal, and additives. The results of sample of 90 paragraphs, consisting of 263 pairs of sentences, 23 (8.75%) pairs of sentences were found to have conjunctural grammatical cohesion, and 240 (91.25%) sentences that didn’t have conjunctural grammatical marker relationships. Keywords: discourse, cohesion, conjunctions, novel.